2018
DOI: 10.1097/paf.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Higher Heart Weight in New Zealand Māori and Pacific Islanders

Abstract: Heart weight is dependent on sex, age, height, and weight. Although previous autopsy studies showed no differences in heart weight between different ethnic groups, none have examined the New Zealand population of Māori and Pacific Islanders (Polynesians). The presented study compared heart weights between 101 European and 85 Polynesian suicide hanging deaths from New Zealand. Univariate linear regression coefficients for age, male sex, height, body weight, body mass index, and Polynesian ethnicity were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Heart weight associates with age, sex, height, weight, body mass index, and ethnicity (3‐13). The heart weight can be compared with reference tables, online calculators, and established reference ranges to determine whether the heart weight is normal or pathological (5,14‐18).…”
Section: Discussionmentioning
confidence: 99%
“…Heart weight associates with age, sex, height, weight, body mass index, and ethnicity (3‐13). The heart weight can be compared with reference tables, online calculators, and established reference ranges to determine whether the heart weight is normal or pathological (5,14‐18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the heart weight of EW15 group was significantly higher than CON group. Heart weight is dependent on sex, age, height, and weight [18]. It may be caused by the relative higher height of EW15 group and not pathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, heart volume was measured by a standard method based on easy to identify landmarks, while the heart mass was measured using a thorough and validated method that removes the confounding influence of water residual from rinsing [ 11 , 12 ]. Finally, previous study of heart mass predictors in a multi-ethnic Aotearoa New Zealand post-mortem cohort found that heart mass can be independently predicted by ethnicity (as a dichotomous variable) when modelled alongside age, male sex, and body size indices [ 3 ]. Case ethnicity, as self-identified in medical records, was not considered as a variable in the current study due to insufficient sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from cardiovascular pathology, heart mass is independently associated with the age and sex of post-mortem cases, as well as with several measures of body size, including body weight and height, and body surface area (BSA) [ 1 , 3 5 ]. These associations have led to the formulation of reference tables or normal ranges for heart mass from easy-to-obtain characteristics and body measures [ 1 , 4 6 ].…”
Section: Introductionmentioning
confidence: 99%